2017
DOI: 10.1096/fj.201700485rr
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase III protects osteocytes from oxidative stress

Abstract: Osteocytes are master orchestrators of bone remodeling; they control osteoblast and osteoclast activities both directly cell-to-cell communication and indirectly secreted factors, and they are the main postnatal source of sclerostin and RANKL (receptor activator of NF-kB ligand), two regulators of osteoblast and osteoclast function. Despite progress in understanding osteocyte biology and function, much remains to be elucidated. Recently developed osteocytic cell lines-together with new genome editing tools-has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Ca3 upregulation was also observed in the easy‐ and difficult‐to‐express protein high producer clones as well as in Foxa1‐overexpressing cells and to a lesser extent in Tagap‐overexpressing cells. Notably, Ca3 was shown to inhibit H 2 O 2 ‐induced apoptosis and to reduce H 2 O 2 ‐induced ROS activity (Raisanen et al, 1999; Shi et al, 2018). It was also shown to protect cells against hypoxic stress (reviewed in Di Fiore et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ca3 upregulation was also observed in the easy‐ and difficult‐to‐express protein high producer clones as well as in Foxa1‐overexpressing cells and to a lesser extent in Tagap‐overexpressing cells. Notably, Ca3 was shown to inhibit H 2 O 2 ‐induced apoptosis and to reduce H 2 O 2 ‐induced ROS activity (Raisanen et al, 1999; Shi et al, 2018). It was also shown to protect cells against hypoxic stress (reviewed in Di Fiore et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that an increase in CA3 inhibited death of osteocytes and nucleus pulposus cells of rats due to hydrogen peroxide, showing that CA3 is an important factor in protecting cell viability against oxidative stress. 62,63 Another study demonstrated that CA3 was decreased in the damaged hepatocytes of adult rats exposed to alcohol, suggesting that CA3 could be a biomarker of hepatocyte injury by alcohol. 64 We also found that chronic treatment of alcohol induced down-regulation of Car3 mRNA in the hippocampus of adolescent rats.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo bone organ cultures have been used extensively to better understand the functions of osteocytes in bone. Using this approach, it was demonstrated that direct effects on osteocytes mediate some of the actions of Parathyroid hormone (PTH) on the skeleton . For instance, the pro‐resorptive actions of PTH are associated with upregulation of the pro‐osteoclastogenic cytokine Rankl .…”
Section: Use Of Ex Vivo Bone Organ Cultures For the Study Of Bone Biomentioning
confidence: 99%
“…More recently, ex vivo osteocyte‐enriched organ cultures were used to study the expression and regulation of carbonic anhydrase III in osteocytes. It was found that carbonic anhydrase III is highly expressed in osteocytes; it is regulated by PTH, and protects osteocytes from oxidative stress …”
Section: Use Of Ex Vivo Bone Organ Cultures For the Study Of Bone Biomentioning
confidence: 99%
See 1 more Smart Citation